PERSEPSI ORANGTUA TENTANG PAUD ( STUDI YAYASAN BINA INSAN MANDIRI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU) - IRMA EVIEDA YANI; INDRAWATI " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
About Early Childhood Education( Studies in BinaInsanMandiriKelurahanSimpangBaruKecamatanTampan KotaPekanbaru). " . Issues discussed in this paper is to describe how the perception of parents about early childhooddevelopment ECD in yayasan Bina Mandiri Kelurahan Simpang Baru Kecamatan Tampan. Perception of parentsis seen through indicators such as : parental knowledge about early childhood development ( ECD ) , the drivingfactors of parents in educating children . population of this study is that parents send their children in earlychildhood , sample used was cluster sampling , the samples were grouped into two , namely : parents who workand do not work . Method used is descriptive quantitative methods with quantitative data analysis and descriptiveexplanation . Instrument filtering data in use is the observation , questionnaires and interviews , and tabulation ofdata contained in a single data tabulations and diagrams . theory applied to problems of parental perceptions aboutearly childhood education is Max Weber's theory of social action that is especially rational action theory andinstrumental support from David Chaney is people's lifestyles industry . The result of the study are in generaldoing the writer can say that parents who send their own children in early childhood mindset developed so thatthey understand about early childhood education. Advanced mindset encourages parents to send their children inearly childhood remain essentially though not compulsory early childhood followed by each child . Factor thatencourages parents to send their children in early childhood is in because of economic factors , lifestyle factors ,busy factors , and academic factorsKeywords : Perception , ECD ( Early Childhood Education ) , Parents